2012
DOI: 10.4049/jimmunol.1200185
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interaction of the Two Related Fungal SpeciesCandida albicansandCandida dubliniensiswith Human Neutrophils

Abstract: Candida albicans, the most common facultative human pathogenic fungus is of major medical importance, whereas the closely related species Candida dubliniensis is less virulent and rarely causes life-threatening, systemic infections. Little is known, however, about the reasons for this difference in pathogenicity, and especially on the interactions of C. dubliniensis with the human immune system. Because innate immunity and, in particular, neutrophil granulocytes play a major role in host antifungal defense, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 71 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…Neutrophils are not simply effective and fast killer/effector cells, but depending on the size and nature of the pathogen they deploy different antimicrobial responses. They can selectively release NETs in response to fungal hyphae and pathogens, which are too large to be phagocytosed (Branzk et al, 2014;Byrd et al, 2013;Svobodova et al, 2012). These DNA-based, web-like structures have effective trapping function and are able to prevent pathogen expansion and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are not simply effective and fast killer/effector cells, but depending on the size and nature of the pathogen they deploy different antimicrobial responses. They can selectively release NETs in response to fungal hyphae and pathogens, which are too large to be phagocytosed (Branzk et al, 2014;Byrd et al, 2013;Svobodova et al, 2012). These DNA-based, web-like structures have effective trapping function and are able to prevent pathogen expansion and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxidants have been suggested to be involved in various defense mechanisms against pathogens, leading to the state of oxidative stress, with significant biological consequences (Lugrin et al, 2014). Different studies have documented high ROS production by neutrophils in response to BV-associated bacteria, C. albicans, and T. vaginalis infection and suggested to play an important role in maintaining low burden of infection (Li et al, 2012b; de Souza Bonfim-Mendonça P, Ratti BA, Godoy JD, 2014; Frasson et al, 2012;Svobodová et al, 2012;Johnson et al, 2017). To assess the status of oxidative stress by studying all oxidants/anti-oxidants parameters is tedious, time-consuming, and uneconomical.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immunity represented by neutrophils and macrophages is believed to serve as the first line of defense by phagocytosis and direct killing of Candida . Furthermore, the antifungal immunity-related IL-17A, which is considered an important component in host defense against Candida infections, produced by peripheral blood mononuclear cells is significantly lower when challenged with C. dubliniensis in vitro [18]. Recently, Krause and colleagues even showed that candidemic patients had significantly higher IL-17A levels compared to non-candidemic patients [19].…”
Section: Discussionmentioning
confidence: 99%